The Application of Eye-Tracking Technology in the Assessment of Radiology Practices: A Systematic Review - Arthur, Elizabeth; Sun, Zhonghua (MDPI AG, 2022)
The aim of this review is to provide an in-depth analysis of literature pertaining to the use of eye-tracking equipment in the evaluation of radiological image interpretation by professionals in clinical practice. A systematic search of current literature was conducted through the databases of CINAHL, Medline, ProQuest, PubMed, Scopus, Web of Science and Wiley Online Library. A total of 25 articles were included in the final analysis. The literature gathered referenced four main discussions, which were competency assessment, educational tools, visual search behaviour and assistive aid evaluations. The majority of articles (68%) referenced to the competency assessment of professional groups yet appeared to have conflicting results within the categories of speed and eye-metrics. Significant conclusions could be made pertaining to confidence (100%) and accuracy measurements (56%), which suggested a background of higher experience correlates to a higher rate of accuracy and a higher confidence level. Other findings regarding the main themes focused on eye-tracking as an educational tool, where the literature suggests that such equipment may be useful in improving educational repertoire and interpretation technique. Literature pertaining to the visual search behaviour analysis and the evaluation of assistive aids did not provide strong conclusions due to research limitations. Whilst the use of eye-tracking in the analysis of radiological practices is a promising new venture to quantify the interpretation patterns of professionals, undertaking future research is recommended to solidify conclusions and provide greater insight.